Perspectives of Canadian Stakeholders on Criteria for Appropriateness for Total Joint Arthroplasty in Patients With Hip and Knee Osteoarthritis. Issue 7 (July 2015) - Hawker, Gillian; Bohm, Eric R.; Conner‐Spady, Barbara; De Coster, Carolyn; Dunbar, Michael; Hennigar, Allan; Loucks, Lynda; Marshall, Deborah A.; Pomey, Marie‐Pascale; Sanmartin, Claudia; Noseworthy, Tom
<x xml:space="preserve">Abstract</x> Objective As rates of total joint arthroplasty (TJA) for osteoarthritis (OA) rise, there is a need to ensure appropriate use. We undertook this study to develop criteria for appropriate use of TJA. Methods In prior work, we used qualitative methods to separately assess OA patients' and arthroplasty surgeons' perceptions regarding appropriateness of patient candidates for TJA. The current study reviewed the appropriateness themes that emerged from each group, and a series of statements were developed to reflect each unique theme or criterion. A group of arthroplasty surgeons then indicated their level of agreement with each statement using electronic voting. Where ≤70% agreed or disagreed, the criterion was discussed and revised, and revoting occurred. In standardized telephone interviews, OA patient focus group participants indicated their level of agreement with each revised criterion. Results Qualitative research in 58 OA patients and 14 arthroplasty surgeons identified 11 appropriateness criteria. Member‐checking in 15 surgeons (including 5 who had participated in the qualitative study) resulted in agreement on 6 revised criteria. These included evidence of arthritis on joint examination, patient‐reported symptoms negatively impacting quality of life, an adequate trial of appropriate nonsurgical treatment, realistic patient expectations of surgery, mental and physical readiness of patient for surgery, and patient‐surgeon agreement that potential benefits exceed risks. Thirty‐six of the original 58 OA patient focus group participants (62.1%) participated in the member‐check interviews and endorsed all 6 criteria. Conclusion Patients and surgeons jointly endorsed 6 criteria for assessment of TJA appropriateness in OA patients. Prospective validation of these criteria (assessed preoperatively) as predictive of postoperative patient‐reported outcomes is under way and will inform development of a surgeon–patient decision‐support tool for assessment of TJA appropriateness.